Pengaruh Pijat Endorphin dan Aroma Terapi Lavender terhadap Tingkat Nyeri Ibu Post Sectio Caesarea - Heti Putri Utami; Mudy Oktiningrum; Kristina Maharani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The rate of deliveries by cesarean section (CS) continues to increase globally and is projected to reach 29% by 2030. Although CS is medically effective in ensuring maternal and neonatal safety, the procedure often results in moderate to severe postoperative pain, which may hinder early mobilization, slow recovery, and reduce the mother’s overall quality of life. Effective pain management is therefore crucial. Non-pharmacological therapies such as endorphin massage and lavender aromatherapy have been recognized as complementary approaches that stimulate the release of relaxation hormones, provide natural analgesic effects, and help reduce anxiety. This study aimed to analyze the effect of combining endorphin massage and lavender aromatherapy on reducing pain levels in post-cesarean section mothers. A quasi-experimental design with a pre–posttest control group was employed. A total of 34 respondents were selected using purposive sampling and divided into intervention and control groups. The study was conducted in the maternity ward of SMC Telogorejo Hospital from March to April 2025. The intervention group received endorphin massage combined with lavender aromatherapy for 10–30 minutes, while the control group was given deep breathing relaxation only. Pain levels were measured before and after the intervention using the Numeric Rating Scale (NRS). Data were collected through questionnaires and medical records, and analyzed using univariate and bivariate techniques with the Mann–Whitney test. Results showed a p-value of 0.000 and Z = -3.774, indicating a significant effect of the intervention. These findings suggest that endorphin massage combined with lavender aromatherapy is effective in reducing postoperative pain. Further studies with larger samples are recommended to explore the optimal duration and frequency of therapy.